METODE DAN TEKNIK PENGENALAN BAHASA INGGRIS UNTUK ANAK USIA DINI PADA KELOMPOK B DI PAUD ISLAM TERPADU BINTANG KABUPATEN BANJAR - Khazijah, Husnul; Izza, Nor Izzatil Hasanah; Rusdiah, Rusdiah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
The rapid development of information and communication today makes English one of the important things that must be learned from an early age in order to prepare future generations who will continue to face a world with various forms of progress. The importance of choosing and using the right methods and techniques in order to create maximum results, therefore this study aims to find out the methods and techniques in the introduction of English in Group B at PAUD Islam Terpadu Bintang Banjar Regency. This research uses a qualitative approach with a type of case study research. The subjects of this study are educators and students of Group B in PAUD Islam Terpadu Bintang and The object of this study is the method and technique of introducing English to Group B in PAUD Islam Terpadu Bintang. This research uses data collection techniques, namely observation, interviews and documentation as well as data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results showed that in implementing the English language recognition program, teachers used 3 methods including: the TPR (total physical response) method, the sing and song method (singing and song), and the habituation method. Teachers also use 4 techniques including: listen and repeat techniques, listen and do techniques, question and answer techniques and modeling and demonstration techniques.